2006
DOI: 10.2298/abs0601013s
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of nucleoside analogs on experimental autoimmune encephalomyelitis in dark agouti rats

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a commonly used animal model of the human neurological disorder multiple sclerosis. The purpose of the present study was to investigate the effect of combined treatment with two nucleoside analogs, ribavirin and tiazofurin, on development of EAE actively induced in highly susceptible dark agouti rats. The obtained results showed that ribavirin and tiazofurin applied either separately or in combination from the onset of the firstsymptoms of EAE after its induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Since previously we confirmed that the coadministration of RBV and TR has a more potent effect in attenuating the clinical signs of EAE than each drug given individually (Stojkov et al, 2006), in this study we used a combined therapeutic approach as well. Consistent with our prior findings (Stojkov et al, 2008), combined RBV+TR treatment significantly suppressed the development of EAE in terms of reducing disease severity, mononuclear cell infiltration and demyelination.…”
Section: Discussionmentioning
confidence: 92%
“…Since previously we confirmed that the coadministration of RBV and TR has a more potent effect in attenuating the clinical signs of EAE than each drug given individually (Stojkov et al, 2006), in this study we used a combined therapeutic approach as well. Consistent with our prior findings (Stojkov et al, 2008), combined RBV+TR treatment significantly suppressed the development of EAE in terms of reducing disease severity, mononuclear cell infiltration and demyelination.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies exploited the fact that ribavirin and tiazofurin inhibit IMPDH via their active metabolites through binding to the enzyme at different sites and trialed them in combination therapy [89][90][91]. Indeed, it was shown that combination therapy was more effective in suppression of the ongoing disease, than each drug used alone.…”
Section: Experimental Autoimmune Encephalomyelitismentioning
confidence: 99%